Metabolic, structural, and proteomic changes in Candida albicans cells induced by the protein-carbohydrate fraction of Dendrobaena veneta coelomic fluid - Marta J. Fiołka (Nature Portfolio, 2021)
Abstract The isolated protein-polysaccharide fraction (AAF) from the coelomic fluid of Dendrobaena veneta earthworm shows effective activity against Candida albicans yeast. Fungal cells of the clinical strain after incubation with the active fraction were characterized by disturbed cell division and different morphological forms due to the inability to separate the cells from each other. Staining of the cells with acridine orange revealed a change in the pH of the AAF-treated cells. It was observed that, after the AAF treatment, the mitochondrial DNA migrated towards the nuclear DNA, whereupon both merged into a single nuclear structure, which preceded the apoptotic process. Cells with a large nucleus were imaged with the scanning electron cryomicroscopy (Cryo-SEM) technique, while enlarged mitochondria and the degeneration of cell structures were shown by transmission electron microscopy (TEM). The loss of the correct cell shape and cell wall integrity was visualized by both the TEM and SEM techniques. Mass spectrometry and relative quantitative SWATH MS analysis were used to determine the reaction of the C. albicans proteome to the components of the AAF fraction. AAF was observed to influence the expression of mitochondrial and oxidative stress proteins. The oxidative stress in C. albicans cells caused by the action of AAF was demonstrated by fluorescence microscopy, proteomic methods, and XPS spectroscopy. The secondary structure of AAF proteins was characterized by Raman spectroscopy. Analysis of the elemental composition of AAF confirmed the homogeneity of the preparation. The observed action of AAF, which targets not only the cell wall but also the mitochondria, makes the preparation a potential antifungal drug killing the cells of the C. albicans pathogen through apoptosis.